Electrochemical evaluation of LiZnxMn2−xO4 (x≤0.10) cathode material synthesized by solution combustion method. Issue 5 (April 2016) - Xu, Wangqiong; Li, Qiling; Guo, Junming; Bai, Hongli; Su, Chang-wei; Ruan, Rongsheng; Peng, Jinhui
Abstract: The spinel LiZn x Mn2− x O4 ( x ≤0.10) cathode materials have been synthesized by solution combustion method at 600 °C for 3 h. The structure and the morphology of LiZn x Mn2− x O4 were characterized by X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM), respectively. All the obtained samples were identified as the spinel structure of LiMn2 O4, the lattice parameters of samples decreased and the particle size increased as the Zn content increased. The effects of Zn-doping on the electrochemical characteristics of LiMn2 O4 were investigated by galvanostatic charge–discharge experiments, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Among them, LiZn0.05 Mn1.95 O4 particles presented outstanding cycling stability with a capacity retention of 82.9% at a discharge rate of 1 C (1 C=148 mA h g −1 ) after 500 cycles. Spinel LiZn0.05 Mn1.95 O4 had reversible cycling performance, revealing that doping LiMn2 O4 with Zn improves its electrochemical performance.